2016
DOI: 10.3168/jds.2016-10959
|View full text |Cite
|
Sign up to set email alerts
|

A study to examine the relationship between metritis severity and depletion of oxytetracycline in plasma and milk after intrauterine infusion

Abstract: Metritis is a frequent problem in postpartum dairy cows. Intrauterine therapy with the antimicrobial oxytetracycline (OTC) is often used, although this therapy has not been shown to be superior to systemic therapy. The objectives of this study were to (1) determine the plasma and milk concentrations of OTC following intrauterine infusion in postpartum dairy cows with varying degrees of metritis severity; (2) determine the depletion time of OTC in an attempt to provide veterinarians withdrawal guidelines, shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…In the present study, tetracycline was present in 22% of all milk samples, but only 1% of all milk samples had concentrations higher than the Canadian MRL of 100 ng/mL. Tetracycline-class drug residues higher than 100 ng/mL have been reported in milk samples after intravenous, intramuscular, subcutaneous, and intrauterine administration (Anderson et al, 1995;Gorden et al, 2016). A study by Rodrigues et al (2010) on 12 cows reported mean milk tetracycline concentrations from 0.1 to 6.2 ng/mL at 8 to 120 h following DD treatment with tetracycline.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…In the present study, tetracycline was present in 22% of all milk samples, but only 1% of all milk samples had concentrations higher than the Canadian MRL of 100 ng/mL. Tetracycline-class drug residues higher than 100 ng/mL have been reported in milk samples after intravenous, intramuscular, subcutaneous, and intrauterine administration (Anderson et al, 1995;Gorden et al, 2016). A study by Rodrigues et al (2010) on 12 cows reported mean milk tetracycline concentrations from 0.1 to 6.2 ng/mL at 8 to 120 h following DD treatment with tetracycline.…”
Section: Discussionmentioning
confidence: 47%
“…Reporting tetracycline concentrations measured in the blood was of notable interest. It is anticipated that, after absorption following extravascular, oral, uterine, or intramammary routes of administration, tetracycline will distribute widely and quickly in the body, reaching low concentrations in plasma (Rodrigues et al, 2010;Gorden et al, 2016). However, we were not able to find relevant information regarding the absorption, distribution, and excretion of antibiotics when administered topically for lameness therapy in dairy cattle (Fajt and Apley, 2001).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations